2014
DOI: 10.3748/wjg.v20.i17.5031
|View full text |Cite
|
Sign up to set email alerts
|

Utility of serum TNF-α, infliximab trough level, and antibody titers in inflammatory bowel disease

Abstract: On the basis of the present study, we suggest that the simultaneous measurement of serum TNF-α level, serum anti TNF-α concentration, and antibodies against anti TNF-α may further help to optimize the therapy in critical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Differences in serum biologic concentrations between ADAb-positive and -negative patients were found to be statistically significant in studies of ADA [4244, 4750, 5355, 57, 58, 61] and INF [54, 57, 58, 61, 8791, 97, 98, 105, 107, 111, 113, 114] across chronic inflammatory diseases. In the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate, a 12-month observational prospective cohort study, ADAbs against ADA were detected in 31 of 160 (19%) ADA-treated patients and were significantly associated with lower ADA concentrations ( r s  = −0.51; p  < 0.0001) [44].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in serum biologic concentrations between ADAb-positive and -negative patients were found to be statistically significant in studies of ADA [4244, 4750, 5355, 57, 58, 61] and INF [54, 57, 58, 61, 8791, 97, 98, 105, 107, 111, 113, 114] across chronic inflammatory diseases. In the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate, a 12-month observational prospective cohort study, ADAbs against ADA were detected in 31 of 160 (19%) ADA-treated patients and were significantly associated with lower ADA concentrations ( r s  = −0.51; p  < 0.0001) [44].…”
Section: Resultsmentioning
confidence: 99%
“…For studies included in this review in which serum levels of biologics were reported – ADM, CZP and IFX – ADAbs-positive patients had lower serum levels of the biologic than ADAbs-negative patients ( Table 2 ). 27 48 …”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetic and/or clinical outcomes (efficacy and/or safety) in ADA‐positive patients were reported in 42 and 40% of adalimumab and infliximab studies, respectively. In 15 of 38 (39%) adalimumab studies and 18 of 62 (29%) infliximab studies , ADA‐positive patients had lower serum concentrations of the biological than ADA‐negative patients. The association between biological serum concentrations and ADA formation was evident in inflammatory disease states and immunoassay formats.…”
Section: Resultsmentioning
confidence: 99%
“…The association between biological serum concentrations and ADA formation was evident in inflammatory disease states and immunoassay formats. Differences in serum concentrations between ADA‐positive and ‐negative patients were found to be statistically significant in nine of 38 (24%) adalimumab studies and 12 of 62 (19%) infliximab studies . For example, in an observational cohort study of 115 patients with AS who received adalimumab, after 24 weeks of treatment serum levels of the biological were significantly higher in ADA‐negative patients than in ADA‐positive patients [12·7 mg/l (interquartile range = 8·2–18·0) versus 1·2 mg/l (0·0–2·0); P < 0·001] .…”
Section: Resultsmentioning
confidence: 99%